Contrasting Electroencephalography-Derived Entropy and Neural Oscillations With Highly Skilled Meditators - Young, Jacob H.; Arterberry, Martha E.; Martin, Joshua P. (Frontiers in Human Neuroscience, 2021)
Meditation is an umbrella term for a number of mental training practices designed to improve the monitoring and regulation of attention and emotion. Some forms of meditation are now being used for clinical intervention. To accompany the increased clinical interest in meditation, research investigating the neural basis of these practices is needed. A central hypothesis of contemplative neuroscience is that meditative states, which are unique on a phenomenological level, differ on a neurophysiological level. To identify the electrophysiological correlates of meditation practice, the electrical brain activity of highly skilled meditators engaging in one of six meditation styles (shamatha, vipassana, zazen, dzogchen, tonglen, and visualization) was recorded. A mind-wandering task served as a control. Lempel-Ziv Complexity showed differences in nonlinear brain dynamics (entropy) during meditation compared to mind-wandering, suggesting that meditation, regardless of practice affects neural complexity. In contrast, there were no differences in power spectra at six different frequency bands, likely due to the fact that participants engaged in different meditation practices. Finally, exploratory analyses suggest neurological differences among meditation practices. These findings highlight the importance of studying the EEG correlates of different meditative practices.